Testing of multiple levels of fermented nitrogen fertilizer dosage and application time interval on oil palm seedling growth - M. Wasito; M. Sidik Tarigan; Sulardi; Sri Mahareni Sitepu (Journal of Information Technology, computer science and Electrical Engineering, 2025)
Oil palm nurseries need nutrients in their growth. This study aims to determine the consequences of administering several levels of Fermented Nitrogen Fertilizer Dosage and the Time Interval of Its Application to the growth of oil palm seedlings (Elaeis Giuneensis Jacq) in the Main Nursery and their interactions. This study used a factorial random group design (RAK) with 2 treatments, namely the administration of the dose of fermented nitrogen fertilizer and the time interval of its application. The first factor is Factor 1, multiple levels of Fermented Nitrogen Fertilizer (F) Dosage consist of F0 = 0 ml/plant, F1 = 50ml/plant, F2 = 100 ml/plant, F3 = 150 ml/leaf plant F4 = 200 ml/plant. Factor 2, the time interval of administration (i), i1 = once a week, i2 = once every two weeks, i3 = once every 3 weeks. The parameters observed were plant height (cm), number of leaves (strands), leaf area (cm2), wet weight sampling (grams), wet weight per plot (grams) and dry weight per sample (grams), dry weight per plot (grams). Based on the results of the research conducted, it can be seen that the consequences of administering several levels of fermented nitrogen fertilizer dosage and the time interval of application have a very real effect on the parameters of plant height, number of leaves, leaf area, and have a noticeable difference in the parameters of the sampling wet weight, wet weight per plot, dry weight of the sample, dry weight per plot, and have a different effect on the interaction between the administration of nitrogen fertilizer dosage levels fermentation and the time interval of its application to all observation parameters.